PENGARUH PERTUMBUHAN EKONOMI, PENGELUARAN PEMERINTAH DAN TINGKAT PENGANGGURAN PEMERINTAH DAN TINGKAT PENGANGGURAN TERBUKA TERHADAP INDEKS PEMBANGUNAN MANUSIA KABUPATEN / KOTA DI PROVINSI KALIMANTAN BARAT - B2051141007, MARIA YOSEPHINA (Jurnal Ekonomi Daerah (JEDA), 2016)
The welfare of society is the goal of development. One starting measuring can be seen through the Human Development Index (HDI), the purpose of this study was to determine how the development of the Human Development Index Regency/City in West Kalimantan Year 2009-2013 and analyze how much influence economic growth, government spending and the Unemployment Rate is open to the human development index districs/cities in West Kalimantan. The result shows the development of the Human Developmetn Indez has increased with the category of medium human development index over the periode 2009-2013 to be able to achieve the target of the Human Development Index established by the government. While the results of multiple linear regression showed economic growth is positive and significant impact on the human development index, government spending and significant positive effect in the human development index, and the open unemployment rate has no effect on the human development index. In conclusion the development of the Human Development Index has increased during the years 2009-2013, a positive effect on economic growth, government spending and positive effect on open unemployment rate of positive influence on the human development index. Through this study suggested that the government’s planning policy is not only seen from the achievement of economic growth, but also a target of increasing human development because economic growth alone is not sufficient to improve the quality of human resources, especially in the aspect of education, health and incomes. Keywords : Economic Growth, Government Spending, Unemployment rate, and the Human Development Index